THE RELATIONSHIP BETWEEN KNOWLEDGE LEVEL AND RATIONAL HEADACHE PAIN SELF-MEDICATION BEHAVIOUR ON FIKES STUDENTS AT LAMONGAN MUHAMMADIYAH UNIVERSITY - Siti Rahmatul Azizah; Irma Susanti; Devi Ristian Octavia (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
The prevalence of self-medication in Indonesia is 84.23%, a figure that has been increasing over the past three years. The increase in self-medication in Indonesia, the availability of drugs that can be taken alone without a doctor's prescription, the perception of mild illness, and the relatively low price of drugs. The potential risks of self-medication are incorrect diagnosis of disease, delay in seeking necessary treatment, disease becoming more severe, wrong method administration, and wrong dose. Knowledge of rational use of drug self-medication still lacks students at 55.5%. It is important to know that student self-medication, in which students can overcome minor complaints of their own illness, does not have an impact on health and academic achievement. The incidence of headaches in students is 11-40% and mild headache levels interfere with academic performance. This study measures level knowledge behavior to determine the relationship between level knowledge and rational headache self-medication behavior by students at Muhammadiyah Lamongan University. The research design was cross-sectional descriptive analytics. Data were collected using online questionnaires. The sample included 166 Fike students using a purposive sampling technique. The results indicated level of knowledge: students classified sufficient (59.0%) and rational head pain self-medication behavior classified as good (57.8%). The results of the Spearman Rho test analysis showed a p-value of <0.001 and correlation coefficient of 0.256. This study concluded that there is a relationship between level of knowledge and rational headache self-medication behavior with low correlation strength.